2020
DOI: 10.1093/gbe/evaa095
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evolutionary Analysis of Nematode Zona Pellucida (ZP) Modules Reveals Disulfide-Bond Reshuffling and Standalone ZP-C Domains

Abstract: Zona pellucida (ZP) modules mediate extracellular protein-protein interactions and contribute to important biological processes including syngamy and cellular morphogenesis. While some biomedically-relevant ZP modules are well-studied, little is known about the protein family’s broad-scale diversity and evolution. The increasing availability of sequenced genomes from “non-model” systems provides a valuable opportunity to address this issue, and to use comparative approaches to gain new insights into ZP module … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 82 publications
0
5
0
Order By: Relevance
“…Recent bioinformatic analysis has enumerated components of the C. elegans ECM (including aECMs), predicting a total “matrisome” of over 700 proteins 10 . The 43 C. elegans ZP proteins have been further classified by phylogenetic methods 11 , 12 . This “parts list” for C. elegans aECMs remains dauntingly complex, with functional or expression data lacking for many proteins.…”
Section: Caenorhabditis Elegans Aecm Components and Biosynthmentioning
confidence: 99%
“…Recent bioinformatic analysis has enumerated components of the C. elegans ECM (including aECMs), predicting a total “matrisome” of over 700 proteins 10 . The 43 C. elegans ZP proteins have been further classified by phylogenetic methods 11 , 12 . This “parts list” for C. elegans aECMs remains dauntingly complex, with functional or expression data lacking for many proteins.…”
Section: Caenorhabditis Elegans Aecm Components and Biosynthmentioning
confidence: 99%
“…Initial surveys of ZP proteins across phyla suggested that some contain ZPn domains without ZPc domains, and yet are still capable of polymerization [36], while proteins with only ZPc domains were not thought to exist [30]. However, we and others found that C. elegans does have five predicted ZPc-only proteins [34,68]. In proteins like uromodulin that have polymerizing ZPn domains, ZPc domains are thought to inhibit the ZPn domain [30].…”
Section: Zpc Domains Can Function Independently Of Zpn Domainsmentioning
confidence: 69%
“…However, we and others found that C . elegans does have five predicted ZPc-only proteins [ 34 , 68 ]. In proteins like uromodulin that have polymerizing ZPn domains, ZPc domains are thought to inhibit the ZPn domain [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The nematode Pristionchus pacificus was established in the 1990's as a comparative system to the model nematode Caenorhabditis elegans (last sharing a common ancestor 80-200 mya) (Howard et al 2022). Having two divergent, experimentally tractable model organisms in the same Order has facilitated functional evolutionary and developmental (evo-devo) studies leading to several unexpected findings (Markov et al 2016;Rošić et al 2018;Beltran et al 2019;Bui and Ragsdale 2019;Hong et al 2019;Weadick 2020;Sun et al 2021;Lo et al 2022). For example, early studies on vulva development revealed the extent of developmental systems drift, whereby the genetic underpinnings of a trait diverge even as the trait itself is conserved (Wang and Sommer 2011;Sommer 2012).…”
Section: Introductionmentioning
confidence: 99%